(untitled) (Computer systems and information technologies, 2020)
promising areas for improving the education system, and with the advent of coronavirus online mode has become critical in education, in this regard are at home. Schools have started using Zoom software, and the role of the modular learning environment has grown significantly. At the same time, many problems were identified, such as the lack of Internet access for students from rural areas or disadvantaged families, which has become an obstacle to learning and access to educational materials. In response, the United Nations Educational, Scientific and Cultural Organization has made a number of recommendations for distance learning. Modern distance education is an extensive system of knowledge transfer at a distance using various tools and technologies, the result of which is the receipt by users of the necessary information for its successful implementation in practice. There are a variety of ways to disseminate knowledge today: mailing books, writing assignments, audio and video discs, telephone consultations, and virtually limitless possibilities of the World Wide Web. The use of distance learning methods allows to provide educational services of various kinds in remote areas, to teach without interruption from the main activity, to teach people with disabilities, to have access to educational resources of the world through the use of modern electronic communications. In today’s world, education plays a key role in people’s lives, which makes it necessary to constantly develop teaching methods, including distance learning. The coronavirus pandemic has revealed many shortcomings of distance education, as well as the absolute unpreparedness of students and educational institutions for this form of education. That is why it is important to develop this industry now in order to further provide comfortable education for both Ukrainian and foreign students and to ensure that in the future the education system will be ready for situations similar to the coronavirus pandemic. The article is written to assess the advantages and disadvantages of distance learning, its necessity, analysis of the requirements for distance learning materials. Prospects of technologies of multimedia representation of researched objects, processes, phenomena, adequate modeling of the subject area, and their realization.